How to predict response to anti-tumour necrosis factor agents in inflammatory bowel disease. - Naviglio, Samuele; Giuffrida, Paolo; Stocco, Gabriele; Lenti, Marco Vincenzo; Ventura, Alessandro; Corazza, Gino Roberto; Di Sabatino, Antonio (Expert Rev Gastroenterol Hepatol, 2018)
INTRODUCTION: Anti-tumor necrosis factor (TNF) agents have changed the therapeutic approach to inflammatory bowel disease (IBD). However, a considerable proportion of patients either do not primarily respond or lose response to treatment. Despite the long-standing experience in the use of these drugs, still there is the need of identifying the possible predictors of efficacy. Areas covered: We critically review the current knowledge on predictors of response to anti-TNF therapy - both those available in clinical practice and those still under investigation. Multiple factors are involved in treatment success, including disease phenotype and severity, adherence to medications, and pharmacogenomic, pharmacokinetic, and immunologic factors. Literature search was conducted in PubMed using keywords 'inflammatory bowel disease,' 'Crohn's disease,' and 'ulcerative colitis,' matched with 'antitumor necrosis factor,' 'biologic therapy,' 'clinical response,' 'predictors,' and 'efficacy,' Relevant articles were selected for review. Expert commentary: While the role of several factors in clinical practice is clearly established, other investigational markers have been proposed, mostly in small studies, yet for many of them little external validation exists. Therapeutic drug monitoring is emerging as a pivotal strategy to guide decisions in clinical practice. In the near future, novel markers could improve our ability to direct treatment and personalize therapy.
Keywords: Antibodies, Monoclonal; Biological Therapy; Gastrointestinal Agents; Humans; Inflammatory Bowel Diseases; Patient Selection; Prognosis; Treatment Outcome; Tumor Necrosis Factor-alpha